RPL6: A Key Molecule Regulating Zinc- and Magnesium-Bound Metalloproteins of Parkinson’s Disease - Anirudhan, Athira; Angulo-Bejarano, Paola Isabel; Paramasivam, Prabu; Manokaran, Kalaivani; Kamath, S. Manjunath; Murugesan, Ram; Sharma, Ashutosh; Ahmed, Shiek S. S. J. (Frontiers in Neuroscience, 2021)
Parkinson’s disease (PD) is a progressive neurodegenerative disease with no definite molecular markers for diagnosis. Metal exposure may alter cellular proteins that contribute PD. Exploring the cross-talk between metal and its binding proteins in PD could reveal a new strategy for PD diagnosis. We performed meta-analysis from different PD tissue microarray datasets to identify differentially expressed genes (DEGs) common to blood and brain. Among common DEGs, we extracted 280 metalloprotein encoding genes to construct proteins network describing the regulation of metalloproteins in PD blood and brain. From the metalloproteins network, we identified three important functional hubs. Further analysis shows RPL6 a novel intermediary molecule connecting the three hubs of the metalloproteins network. Quantitative Real-time PCR analysis showed RPL6 was down regulated in PD peripheral blood mononuclear cells (PBMC) samples. Simultaneously, trace element analysis revealed altered serum zinc and magnesium concentrations in PD samples. The Pearson’s correlation analysis shows that serum zinc and magnesium regulates the RPL6 gene expression in PBMC. Thus, metal regulating RPL6 act as intermediary molecule connecting the three hubs those are functionally associated with Parkinson’s disease. Overall, our study explores the understanding of metal-mediated pathogenesis in PD, which provides a serum metal environment regulating the cellular gene expression that may light towards metal and gene expression based biomarkers for PD diagnosis.